A randomized controlled study of power posing before public speaking exposure for social anxiety disorder: No evidence for augmentative effects. (December 2017) - Davis, Michelle L.; Papini, Santiago; Rosenfield, David; Roelofs, Karin; Kolb, Sarah; Powers, Mark B.; Smits, Jasper A.J.
Highlights: Power posing (compared to submissive posing/rest) did not result in changes in testosterone. Power posing (compared to submissive posing/rest) did not result in changes in cortisol or fear during an exposure. Power posing (compared to submissive posing/rest) did not facilitate exposure therapy outcomes for social anxiety disorder. Abstract: This manuscript details a randomized controlled study designed to test the efficacy of power posing (i.e., briefly holding postures associated with dominance and power) as an augmentative strategy for exposure therapy for social anxiety disorder (SAD). Seventy-three individuals diagnosed with SAD were assigned to one of three conditions: power posing, submissive posing, or rest (no posing) prior to participating in an exposure therapy session. Participants were assessed for between-group differences in pre- and post-manipulation salivary hormone levels, within-session subjective experiences of fear, and pre- and 1-week post-treatment SAD severity outcome measures. Though the intervention resulted in decreased SAD symptom severity one week later, analyses revealed no significant between-group differences on any tested variables. Accordingly, this study provides no evidence to suggest that power posing impacts hormone levels or exposure therapy outcomes.